A blue-eyed daisy Newbery Medal-Winning Author of Missing May - Rylant, Cynthia (New York, N.Y. : Bradbury Press, 1985)
Relates episodes in the life of eleven-year-old Ellie and her family who live in a coal mining town in West Virginia.
800
Keywords: Family life -- Fiction; West Virginia -- Fiction